Pengaruh Edukasi Kesehatan Obesitas Melalui Audio Visual Aid (AVA) terhadap Perilaku Pasien Obesitas di Wilayah Puskesmas Melayu Kota Piring Kota Tanjungpinang - Nurhidayu Nurhidayu; Syamilatul Khariroh; Lili Sartika Sartika (STIKes Surya Global Yogyakarta, 2022)
Background of Study: Obesity is an excessive accumulation of fat due to an imbalance of energy intake with energy used for a long time and has an impact on health problems and decreased quality of life. Health education using audio visual aid (AVA) can improve behavior change in obese patients towards a better understanding of health. This study aims to determine the effect of health education through audio visual aid (AVA) on behavioral changes in obese patients in Puskesmas Melayu Kota Piring.Methods: This research used Pre-experimental research design with One Group Pretest Post-test design. There were 20 respondents for sampling. The instrument data used questioner to measure knowledge, attitudes and actions about behavior change. Analysis data used Wilcoxon statistical test.Results: For statistical test knowledge indicators p-value = 0.055 (˃0.05), this showed that the alternative hypothesis (Ho) was rejected. As for the attitude indicator, the statistical test value of p-value = 0.025 (˂0.05) and the indicator of statistical test action p-value = 0.004 (˂0.05), this showed that the alternative hypothesis (Ha) was accepted. Conclusion: Health education through audio visual aid (AVA) can influence the behavior of obese patients.Keywords : health education, audio visual aid (AVA), obesity